Last updated at Dec. 23, 2019 by Teachoo

Transcript

Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (i) If P = {m, n} and Q = { n, m}, then P Q = {(m, n),(n, m)}. P = {"m, n" } Q = {"n, m" } P Q = {"m, n" } {"n, m" } = {(m, n), (m, m), (n, n), (n, m)} Hence. P Q {(m, n),(n, m)}.Hence, the given statement is false. The correct statement is If P = {m, n} and Q = { n, m}, then P Q = {(m, n), (m, m), (n, n), (n, m)} Ex2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (ii) If A and B are non-empty sets, then A B is a non-empty set of ordered pairs (x, y) such that x A and y B. By definition of cross product, Given two non-empty sets A and B A B = {"( x, y); x A , y B" } Hence the given statement is true. Ex 2.1, 4 State whether each of the following statements are true or false. If the statement is false, rewrite the given statement correctly. (iii) If A = {1, 2}, B = {3, 4}, then A (B ) = B = {"3, 4" } B = {"3, 4" } = A (B ) = {"1, 2" } = Hence, the given statement is true.

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.